Standardization of Good Manufacturing Practice-compliant production of bone marrow-derived human mesenchymal stromal cells for immunotherapeutic applications - Wuchter, Patrick; Bieback, Karen; Malcherek, Georg; Saffrich, Rainer; Buß, Eike Christian; Horn, Patrick; Schmitt, Anita; Ho, Anthony Dick; Schmitt, Michael (Cytotherapy, 2015)
Background aims: Human mesenchymal stem or stromal cells (MSCs) represent a potential resource not only for regenerative medicine but also for immunomodulatory cell therapies. The application of different MSC culture protocols has significantly hampered the comparability of experimental and clinical data from different laboratories and has posed a major obstacle for multicenter clinical trials. Manufacturing of cell products for clinical application in the European Community must be conducted in compliance with Good Manufacturing Practice and requires a manufacturing license. In Germany, the Paul-Ehrlich-Institut as the Federal Authority for Vaccines and Biomedicines is critically involved in the approval process. Methods: This report summarizes a consensus meeting between researchers, clinicians and regulatory experts on standard quality requirements for MSC production. Results: The strategy for quality control testing depends on the product's cell composition, the manufacturing process and the indication and target patient population. Important quality criteria in this sense are, among others, the immunophenotype of the cells, composition of the culture medium and the risk for malignant transformation, as well as aging and the immunosuppressive potential of the manufactured MSCs. Conclusions: This position paper intends to provide relevant information to interested parties regarding these criteria to foster the development of scientifically valid and harmonized quality standards and to support approval of MSC-based investigational medicinal products.